EKSPERIMENTAL PENGARUH UKURAN SARINGAN PADA MESIN PENGHALUS ARANG TEMPURUNG KELAPA TERHADAP KARAKTERISTIK BRIKET - Murdani, Murdani; Kurniawan, Irwan; Martianis, Erwen; Hakim, Apriman (INOVTEK POLBENG, 2023)
This research aims to investigate the effect of mesh size on the coconut shell charcoal grinder machine on the grinding time and the quality of the produced briquettes. We tested different mesh screen sizes to determine the optimal grinding time and their impact on the briquettes' characteristics, including density, compressive strength, and combustion efficiency. The research results show that the sieve size has a significant impact on the grinding time and the quality of the briquettes. A 0.5 mm sieve results in the longest grinding time, while a 1 mm sieve provides the fastest grinding time. The smaller the sieve size, the longer it takes to achieve the desired fineness. Other factors such as compressive strength and combustion still influence the quality of the produced briquettes, even though the 1 mm sieve increases time efficiency. Therefore, we recommend using the 1 mm sieve for time efficiency, but further testing is necessary to ensure optimal briquette quality, particularly in terms of density and combustion efficiency.